Regional gradient controllability of parabolic systems - Zerrik, El Hassan; Boutoulout, Ali; Kamal, Asmae (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to show for parabolic systems how one can achieve a final gradient in a subregion [mała litera omega] of the system domain [duża litera omega]. First, we give a definition and delineate some properties of this new concept, and then we introduce the concept of regionally gradient strategic actuators. The importance of the spatial structure and location of the actuators in achieving regional gradient controllability is emphasized.
Keywords: parabolic systems; regional gradient controllability; G-strategic actuator